Political Strategy of The Pks Faction in Advocating Public Aspirations in The North Sumatra Provincial DPRD - Aprilinda M. Harahap; Syahrina Suhilah Siregar; Lolo Ate Karina Berutu; Lia Agita Sari; Andre Selamat Sinaga; Alwi Hadad Nasution; Thorieq Al Abdu (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2026)
This study aims to analyze the political strategies implemented by the Partai Keadilan Sejahtera faction in advocating community aspirations within the North Sumatra Provincial Regional House of Representatives. The research employs a qualitative approach using a descriptive method. Data were collected through interviews, observation, and documentation. Interviews were conducted with Hannah May Lisa as a PKS staff member and Riduansyah as a faction expert staff at the DPRD Secretariat of North Sumatra. The results indicate that the PKS faction’s political strategy in advocating public aspirations involves several stages: gathering community aspirations through recess activities and direct communication with constituents, internal faction discussions to determine priority issues, and political communication and collaboration with other factions and the regional government. In addition, the role of faction expert staff is essential in providing policy analysis and supporting data for the decision-making process. Therefore, faction political strategies play an important role in ensuring that public aspirations are accommodated in regional public policies.